2017
DOI: 10.1515/anre-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity, central obesity, and associated socio-demographic variables in Syrian women using different anthropometric indicators

Abstract: The prevalence of overweight and obesity is increasing globally in both developing and developed countries, especially, those with rapid cultural and social changes. The aims of current study were twofold: (a) to examine, for the first time in Syria, the prevalence of overweight, obesity and central obesity in Syrian women and obesity-related socio-demographic determinants, and (b) to establish a base line data about obesity related determinants needed to develop appropriate treatment and prevention strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…This study found significant positive association between CO and age as well as parity. This finding is consistent with findings from other earlier studies [9] [11] [24]. Transient insulin resistance during pregnancy that encourage intraabdominal fat accumulation may explain higher central obesity in women with higher parity [27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study found significant positive association between CO and age as well as parity. This finding is consistent with findings from other earlier studies [9] [11] [24]. Transient insulin resistance during pregnancy that encourage intraabdominal fat accumulation may explain higher central obesity in women with higher parity [27].…”
Section: Discussionsupporting
confidence: 93%
“…Rising trends in central obesity have been found in populations of different countries [8]. A study among Syrian women found central obesity as defined by WC was higher than BMI derived obesity [9]. Some studies have associated high prevalence of central obesity among women with such physiological processes as child bearing [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the overall prevalence of CO was 61.6% based on WHR cut-offs wherein females were more centrally obese than males (87.2% vs. 35.7%). This result was found to be similar with some previous studies (Abolfotouh et al 2008;Sarkar et al 2009;Nalawade and Prabhu 2012;Kaur et al 2013;Bindhu et al 2014;Goon et al 2014;Siddiquee et al 2015;Chauhan et al 2015;Veghari et al 2016;Bakir et al 2017;Nagendra et al 2017). On the other hand males have shown consistently lower prevalence in comparison to females in all the mentioned studies.…”
Section: Discussionsupporting
confidence: 92%
“…Obesity is considered as a major underlying risk factor of these diseases 5,6 . Alarmingly, data from 2017 suggests a high and potentially rising prevalence of overweight and obesity within the Syrian population 7 .…”
Section: Introductionmentioning
confidence: 99%